2017
DOI: 10.1097/inf.0000000000001677
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Birth HIV-PCR Testing on the Uptake of Follow-up Early Infant Diagnosis Services in Cape Town, South Africa

Abstract: Introduction PCR testing at birth (‘birth-testing’) is suggested by new World Health Organization guidelines for rapid diagnosis of infants infected with HIV in utero. However there are few data on the implementation of this approach in sub-Saharan Africa and whether birth-testing affects uptake of subsequent routine early infant diagnosis (EID) testing at 6–10 weeks of age is unknown. Methods We reviewed 575 consecutive infants undergoing targeted high-risk birth-testing in Cape Town, South Africa, and matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 27 publications
(25 reference statements)
4
30
2
Order By: Relevance
“…Although the uptake of EID testing in the ACC model was high, preliminary data analysis of the national EID data 2018 found that about one-fifth of HIV-exposed infants who were tested received a PCR test at birth, but did not return for the second PCR (GAM report 2018, unpublished). This is consistent with a study in South Africa that reported implementing PCR at birth lowered the uptake of subsequent EID testing at six weeks of age [25]. Details of Thailand's national EID programme, PCR at birth and outcomes of infants receiving birth testing will be reported in separate papers.…”
Section: Discussionsupporting
confidence: 87%
“…Although the uptake of EID testing in the ACC model was high, preliminary data analysis of the national EID data 2018 found that about one-fifth of HIV-exposed infants who were tested received a PCR test at birth, but did not return for the second PCR (GAM report 2018, unpublished). This is consistent with a study in South Africa that reported implementing PCR at birth lowered the uptake of subsequent EID testing at six weeks of age [25]. Details of Thailand's national EID programme, PCR at birth and outcomes of infants receiving birth testing will be reported in separate papers.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the additional column populating the RTHB identifiers incorporated in the consolidated weekly HIV PCR Results for Action Report, allowed continuous monitoring of uptake and usage of RTHB identifiers among all of the public health facilities in the district. Interestingly, the intra-uterine and intrapartum infection rates among the RTHB identifier cohort are similar to near-contemporaneous birth cohorts described in SA, [7,8] supporting the potential use of RTHB identifiers for EID surveillance.…”
Section: Discussionsupporting
confidence: 61%
“…Our study provides additional evidence that receipt of birth HIV‐PCR decreased the presentation for follow‐up testing . Receipt of birth EID reduced the likelihood of subsequent HIV testing after six weeks by 82%, even when controlling for other risk factors.…”
Section: Discussionmentioning
confidence: 59%
“…The detection rate between birth and six to ten weeks was lower than at birth (1%) except in period 3; this compares with rates of 0.4 to 0.5% in a hospital cohort during the same period of targeted birth testing . During period 3 there were no positive birth HIV‐PCR results and the detection rate between birth and six to ten weeks was 2.4% (vs. national rates of 1.4% at six weeks .)…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation